Refleksi Budaya Hukum Pelaku Usaha Pangan Pacsa Kebijakan Sertifikasi Halal - Wahid, Sholeh Hasan (Fakultas Syari'ah Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo., 2024)
This research aims to fill the knowledge gap and offer novel insights into the implementation and legal conduct related to halal certification policies among players in the food industry in Indonesia. The study's value lies in the potential to provide useful recommendations to stakeholders like the government, certification agencies, and MSMEs (Micro, Small, and Medium Enterprises), with the objective of increasing awareness and implementation of halal certification in Indonesia. Although halal certification regulations have been in place since 2014, there seems to be a discrepancy in awareness and comprehension among producers. The study aims to comprehend why there are varied levels of knowledge and compliance with halal certification regulations among producers and what factors contribute to these disparities. The researchers used a qualitative methodology and conducted in-depth interviews with seven business operators representing various sectors within the food industry. Their analysis delved into the legal culture theory to gain insight into producers' understanding and behavior regarding halal certification regulations. The research outcomes suggest a discrepancy in the level of halal certification regulation awareness among producers. Despite the existence of regulations since 2014, some producers remain noncompliant and uninformed of these rules. Besides, certain producers, dedicated to upholding product quality, might not wholly comprehend the protocol and procedures of halal certification. These results support earlier claims of an information deficiency among MSMEs and emphasize the crucial role of ongoing education and support for producers in the context of obtaining halal certification in Indonesia.